Agama Hindu Bali Dalam Kontestasi Budaya - Ida Bagus Made Satya Wira Dananjaya (Universitas Mahendradatta Denpasar, 2019)
Traditions that have been going on for so long and acknowledged their sacredness,tradition provides a reference to life with repetitive rhythms, the majesty of harmony,thus abandoning conflict. Religion gives sacred values to the tradition so that it can gainreinforcement at the mental level into a socio-mythical space. Whereas modernity haveinjects for new ideas, which have an implication of the melting of the state barrier. Modernityunfolds human consciousness about time which is no longer repetitive but is linear,no longer sacred but secular where creative progress and alternatives are created. Traditionand Religion is a mythical-expressive culture that is challenged by progressive-creativeglobal culture coming through tourism. The politics of synergy has been carried outfor a positive vision for people’s lives. However, these three factors cannot be reconciledjust like that, cultural contestation becomes a necessity.